Comparison of the efficiency of different eradication treatments to minimize the impacts caused by the invasive tunicate Styela plicata in mussel aquaculture - Santos, Pedro M. (2023)
In 2017, aquaculture producers of the Albufeira lagoon, Portugal, reported an invasion of tunicates that was disrupting mussel production, particularly the tunicate Styela plicata (Lesueur, 1823). A totally effective eradication method still does not exist, particularly for S. plicata, and the effects of the eradication treatments on bivalves’ performance are also poorly understood. Our study examined the effectiveness of eradication treatments using three laboratory trials and five treatments (air exposure, freshwater immersion, sodium hypochlorite, hypersaline solution and acetic acid) for S. plicata, as well as their effects on survival and growth of blue mussel Mytilus edulis Linnaeus, 1758. While air exposure and freshwater immersion caused a 27% mortality rate in S. plicata, the acetic acid treatment was the most effective in eliminating this species (>90% mortality). However, a 33–40% mortality rate was registered in mussels. Both species were not affected by the hypersaline treatment in the last trial, but the sodium hypochlorite treatment led to a 57% mortality rate in mussels. Differences in mussels’ growth rates were not detected. These trials represent a step forward in responding to the needs of aquaculture producers. However, further studies are needed to investigate the susceptibility of tunicates to treatments according to sexual maturation, as well as to ensure minimum mussel mortality in the most effective treatments, and to better understand the effects on mussel physiological performance in the long-term.